Handbook for writing proposals - Hamper Robert J. (Illinois: NTC Publishing Group, 1995)
This book will help you discover how to find bids, how to evaluate bids and how to develop winning proposals, including personal client presentation. A guide for writing effective business proposals.
Chapter1. Where to begin -- Chapter2. 9-step proposal process -- Chapter3. Selecting the bid and choosing the proposal team -- Chapter4. Finding your unique selling point -- Chapter5. Developing your program design -- Chapter6. Writing the front matter and executive summary -- Chapter7. Producing your proposal -- Chapter8. Making client presentations
Includes index.
Keywords: BUSINESS PROPOSAL; PROPOSAL WRITING